Exploring association between ambient air pollution and glaucoma in China: a nationwide analysis with predictive modeling based on the China Health and Retirement Longitudinal Study - Li, Xiang; Luo, Zhan-Yang; Lei, Sen; Zhang, Zhi-Jie; Tang, Jia-feng; Sun, Yi-qing (Frontiers in Public Health, 2025)
BackgroundGlaucoma, a leading global cause of blindness, has garnered increasing research attention in recent years concerning its potential association with environmental factors. This study investigates the influence of various environmental pollutants on glaucoma prevalence among middle-aged and older adult populations in China, a country with a high incidence of the disease.MethodsUsing data from 17,184 participants in the 2015 China Health and Retirement Longitudinal Study (CHARLS), individuals were grouped based on glaucoma diagnosis. Environmental pollutant exposure levels were derived from satellite-based spatiotemporal models. Standardized linear regression and restricted cubic spline (RCS) analysis were applied to evaluate the impact of pollutants on glaucoma across different covariate-adjusted models, while logistic regression was used to assess significant variables for constructing and evaluating a predictive model.ResultsAfter adjusting for covariates, six pollutants (PM2.5, PM10, PM1, NH4, Cl, and NO3) demonstrated significant associations with glaucoma incidence. Subsequent logistic regression revealed that the occurrence of glaucoma may be influenced by a combination of environmental pollutants (NH4 and NO3), regional categories, gender, age, educational level, and diabetes history.ConclusionIn conclusion, this study offers a novel perspective on glaucoma risk prediction by integrating environmental pollutants, potentially contributing to enhanced preventive strategies for this condition.